2006
DOI: 10.15560/2.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Fish, Piquiri River, Upper Paraná River basin, Paraná state, Brazil

Abstract: The Piquiri River hydrographic basin includes a drainage area of 31,000 km 2 . Headwaters are located in the São João Mountains, flowing 485 km until the Paraná River. The most important tributaries of the right margin are the rivers Goioerê, Tricolor and Cantú, while in the left margin the rivers Sapucaí and Melissa stand out. Six samplings were done between October 2002 and September 2003, in three sampling sites (Campina, Apertado and Altônia) along the Piquiri River. Fish species were collected using gill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 1 publication
(2 reference statements)
0
8
2
1
Order By: Relevance
“…The current survey discloses a much higher number of fish species than that recorded by Gubiani et al (2006Gubiani et al ( , 2010, who reported 62 and 69 species in 2006 and 2010, respectively. This new update represents a nearly 120% increase in the number of species recorded in the basin since the last list was released.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…The current survey discloses a much higher number of fish species than that recorded by Gubiani et al (2006Gubiani et al ( , 2010, who reported 62 and 69 species in 2006 and 2010, respectively. This new update represents a nearly 120% increase in the number of species recorded in the basin since the last list was released.…”
Section: Discussioncontrasting
confidence: 46%
“…Agostinho et al (1997Agostinho et al ( , 2004) registered 57 species. In Gubiani et al (2006), the number increased to 62 species. Later, in Gubiani et al (2010), 69 species were recorded.…”
Section: Introductionmentioning
confidence: 99%
“…There are 110 species in the Tibagi River basin (Shibatta et al 2002), 76 in the Pirapó River basin (Pagotto et al 2012), 62 in the Piquiri River basin (Gubiani et al 2006), 54 in the Jordão River basin (Frota et al in prep. ) and 48 in the Areia river basin (Frota et al in prep.).…”
Section: Discussionmentioning
confidence: 99%
“…Benedito-Cecilio & Agostinho (2000) studied the distribution, abundance and use of different environments by dominant ichthyofauna in the influence area of Itaipu Reservoir. Gubiani et al (2006) showed an updated list of the species registered for the Piquiri River, which was complemented by Stanger (2007) in an ichthyofaunistic survey, and Gubiani (2006) that studied the temporal and spatial variations in the composition and abundance of the ichthyofauna in the Piquiri River. Rezende Neto (2004) raised the number of species to approximately 80 and, as stated by this author, Iheringichthys labrosus was the second species in abundance.…”
Section: Introductionmentioning
confidence: 99%